Issue Information. Issue 9 (28th September 2021) - Unknown
Abstract : Cover : Cell populations at the bottom of intestinal crypts share a similar nutritional environment while displaying distinct metabolic features, representing an ideal model for studying their inherent metabolic characteristics. In this issue, Gebert et al . use intestinal crypts as an example to explain how to cross‐reference transcriptome and proteome data, and use it as an exploratory tool to identify cell‐type‐specific metabolic features. The cover image shows an isolated intestinal crypt stained for polyamine metabolites (red), mitochondria (green), and nuclei (blue), highlighting the heterogeneity of cell metabolism at single‐cell resolution. Image acquired by Shahadat Rahman, Evan Cromwell, and Joanna Smeeton.